ANALISIS STRATEGI PEMASARAN LAYANAN POS EXPRESS PADA PT. POS INDONESIA (PERSERO) MAKASSAR - Mariana Mariana; Edi Jusriadi; Nurlina Nurlina (Universitas Muhammadiyah Makassar, 2019)
This study aims to identify internal factors that are strengths and weaknesses as well as external factors that become opportunities and threats for PT. The results of this study are the formulation of marketing strategies in terms of Pos Express Services, namely attracting business customers. The first thing to do in a marketing strategy is to look at market needs first. Then determine the market segment to be addressed. By choosing a target that matches the market segment then the market position will automatically become the label for the product itself in the community. Marketing Mix in marketing strategies will automatically follow the flow of segmentation, targeting and positioning, because in determining products, places, prices, promotions and processes according to market segments. Demonstrate that the Post Express Service Marketing Strategy at PT. Pos Indonesia (PERSERO) Makassar is right, where the Marketing Strategy used by PT. Pos Indonesia has achieved the desired and appropriate goals in facing business competition, as well as with Post Express Services at PT. Pos Indonesia has been implemented well. Based on the IFAS and EFAS tables if they are contained in a SWOT analysis diagram, the company's position is in the second quadrant, where the strength possessed by Pos Indonesia can be used to deal with threats that overflow the company.